How the psychological safety of healthcare teams relates to team performance, specifically patient outcomes in an acute private hospital in Mpumalanga, South Africa - Nel,Karen (University of Pretoria, 2026)
Mini Dissertation (MBA)--University of Pretoria, 2025.